KEBIJAKAN EKSPOR KAKAO INDONESIA DAN GHANA TERHADAP PASAR EROPA TAHUN 2013-2018 - Refin Satrio (2021)
Cocoa is one of the important commodities that has contributed significantly to the Indonesian economy, which is ranked as the third largest cocoa producing country in the world. However, Ghana as a cocoa producing country whose position is closest to and relatively the same as Indonesia in terms of politics, economy, and cocoa has a competitive advantage that Indonesia does not have. These advantages make Ghana's cocoa products appear superior with quality, productivity, and cocoa export value that is much higher than indonesia, especially in terms of its export trade to the European Union market. The purpose of this study was to determine the differences in export policies between Ghana and indonesia towards the European Union cocoa market, which is the largest chocolate consumer region in the world. The research method used by the author is qualitative research with analytical descriptive research and comparative studies and is supported by competitive advantage theory, strategic trade policy theory, and the concept of economic diplomacy. From this research, the author found that Indonesia has great cocoa potential to be developed and can still learn from what Ghana has presented in terms of cocoa exports. Both from a political or economic perspective, especially towards European Union cocoa market.